CORPORATE GOVERNANCE DAN KINERJA KEUANGAN (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2008-2012) - Laksana, Jaya (E-Jurnal Akuntansi, 2015)
This study aimed to examine the effect of corporate governance on the bank's financial performance. Indicators of corporate governance mechanisms is proxied by the number of board of directors, the proportion of independent board, managerial ownership as an internal and external institutional ownership as a mechanism. While the measurement of financial performance is measured by Return on Assets (ROA). This research was conducted on the entire banking companies listed in Indonesia Stock Exchange 2008-2012 period. The analysis technique used is multiple linear regression. Based on the analysis results it is known that the amount of positive influence on the board of directors of a company's financial performance and managerial ownership negatively affect the financial performance of the banking company in Indonesia Stock Exchange (IDX) the period of 2008-2012, while the proportion of independent board and institutional ownership has no significant effect on the financial performance banking company in Indonesia Stock Exchange (IDX) the period of 2008-2012.
Keywords: corporate governance; board of directors; managerial ownership; the proportion of independent board; institutional ownership; financial performance.